4.3 1,3-Dipolar Cycloadditions of Alkenes - Svatunek,D.; Houk,K. N. (Click Chemistry, 2022)
Click reactions between 1,3-dipoles and alkenes are appealing due to their versatility, which goes beyond simple conjugation applications and the synthesis of five-membered heterocycles. Leveraging various 1,3-dipoles and alkenes, photoactivatable, highly reactive, and “click to release” systems have been developed. In this article, we explore the wide range of reactivities, selectivities, and applications offered by this class of cycloadditions.
Keywords: Referencework; 1,3-dipoles; alkenes; click reactions; click chemistry; cycloadditions